2017
DOI: 10.1111/pace.13004
|View full text |Cite
|
Sign up to set email alerts
|

Active Atrial Function and Atrial Scar Burden After Multiple Catheter Ablations of Persistent Atrial Fibrillation

Abstract: Active LA function is preserved but significantly impaired and associated with ablation-related LA scar burden after multiple extensive persAF ablations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“… 12 Findings of significant impairment of active LA function and its correlation with LA scar as assessed by cardiac MRI and voltage mapping by EAM in patients subjected to multiple CAs compared to ablation-naïve patients suggest that CA per se results in increased LA scar burden with consecutively impaired active LA function. 13 However, in the absence of large studies with serial measurements of atrial scars and function, one cannot completely disregard the role of underlying atriopathy contributing to the atrial scar and deteriorating function.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Findings of significant impairment of active LA function and its correlation with LA scar as assessed by cardiac MRI and voltage mapping by EAM in patients subjected to multiple CAs compared to ablation-naïve patients suggest that CA per se results in increased LA scar burden with consecutively impaired active LA function. 13 However, in the absence of large studies with serial measurements of atrial scars and function, one cannot completely disregard the role of underlying atriopathy contributing to the atrial scar and deteriorating function.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis identified on cardiac magnetic resonance imaging was proven to be an independent factor associated with AF recurrence after CA [13]. Furthermore, a left atrial scar burden after multiple extensive CA was reported [14]. Therefore, we anticipated that the patients in the CA group would be in a more advanced atrial remodeling state with repeated CA, which might lead to a lower chance of normal sinus rhythm recovery than those in the nCA group.…”
Section: Discussionmentioning
confidence: 99%
“…As the duration of AF increases, there tends to be more adverse LA remodelling, resulting in more scar formation, and greater LA stunning despite restoration of SR following ablation. 102,154,155 Using echocardiography, this LA substrate remodelling may be assessed most effectively by measuring strain and less so by evaluating myocardial tissue velocities using TDI 156,157 or volume-derived measurements of left atrial function. Left atrial function as assessed by volumes and strain analysis in our study population was markedly reduced at baseline and improved following ablation.…”
Section: Predictors Of Atrial Fibrillation Recurrencementioning
confidence: 99%
“…It is thought that, in LSPAF patients, the advanced electroanatomical remodelling, along with metabolic and neurohormonal alterations, cause irreversible changes in the LA through fibrosis and post-ablation stunning, which often accompanies early recurrences of AF following ablation. 89,90,99,100 Timely assessment of the left atrial function helps determine the best treatment strategy, as well as the success of ablation 87,[101][102][103][104] or cardioversion. [105][106][107][108][109] Evaluating left atrial reservoir, conduit and contractile function can also be helpful in predicting left atrial electromechanical stunning, which can lead to thromboembolic events.…”
Section: Introductionmentioning
confidence: 99%